Early Dutch and English voyages to Spitsbergen in the seventeenth century : including Hessel Gerritsz 'Histoire du pays nommé Spitsberghe, ' 1613 and Jacob Segersz van der Brugge 'Journael of dagh register, ' Amsterdam, 1634 /: including Hessel Gerritsz 'Histoire du pays nommé Spitsberghe, ' 1613 and Jacob Segersz van der Brugge 'Journael of dagh register, ' Amsterdam, 1634. (2017) - Soulsby, Basil Harrington, 1864-1933; De Villiers, J. A. J (John Abraham Jacob), 1863-1931
No abstract available